Manajemen Pembelajaran Di Perguruan Tinggi Pada Masa Pandemi Covid-19: Manajemen Pembelajaran Di Perguruan Tinggi Pada Masa Pandemi Covid-19 - Dami (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
The purpose of this study was to determine the management of online learning in universities. The form of descriptive qualitative research. Literature study data collection techniques or documentation and observation. The online learning that is currently being implemented certainly needs to be managed because this has only been implemented since the pandemic. The learning system requires us to be innovative and creative because conventional and virtual learning must have different management. The existence of the Covid-19 pandemic requires every university to be able to carry out online learning. The application of this learning definitely requires strategic learning management with the existence of learning designs and supporting facilities. The results of existing research that online learning management can be done include planning, mobilizing, organizing, and supervising. In addition, the application of online learning can include several aspects, namely learning design, learning activities, learning strategies, learning media and technology, and learning assistance services. The advantages of strategic learning management are (1) management functions as a reference in carrying out tasks (2) makes leadership elements and educators and education staff guard against threats in the era of globalization to universities and can be more creative and innovative in facing learning developments and challenges. era of digitalization. (3) leadership elements can provide logical reasons for priority employee placement (4) management can integrate various decisions about certain ways made by several leadership elements in various positions in universities. (5) create an attitude in management that is more productive and developmentally appropriate. Learning at universities is in the process of managing obstacles in the field based on survey data that not all universities in Indonesia have NGOs, unstable electricity conditions so that the network becomes a problem in online learning, especially in the West Kalimantan area.